Early-strength, high-strength and high-wear-resistance aluminoferrite cementing material and preparation method thereof

By solidly dissolving Na, P, B and Sm elements in the ferroalaluminate gelling material and quenching after calcination to stabilize the α'-C2S mineral phase, the inverted strength and hydration of the ferroalaluminate gelling material are solved. The problem of low activity achieves the early high strength and wear resistance of gelled materials.

CN119461909APending Publication Date: 2025-02-18SHANDONG SHANLV CEMENT CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411691060.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-11-21
Filing Date
2024-11-25
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The Fe2O3 content of ferroaluminate gelling materials is high during calcination, resulting in a decrease in mineral hydration activity and inverted strength. The hydration activity of β-type C2S is lower than that of α-type C2S, resulting in a slow growth in the later stage of the gelling materials. Retracted.

Method used

By solidly resolving Na, P, B and Sm elements in calcium sulfhydryl aluminate and calcium ferroalaluminate, the oxygen activity sites of the mineral are increased, the hydration activity is improved, and quenched after calcination to stabilize the α'-C2S mineral phase , improve the early mechanical strength of gelled materials.

Benefits of technology

The strength inverted phenomenon of ferroalaluminate gelling materials is effectively avoided, the stability of the α’-C2S mineral phase and the early mechanical strength of the gelling materials are improved, and wear resistance is significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119461909A_ABST
    Figure CN119461909A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of cementing material clinker preparation, and particularly discloses an early-strength, high-strength and high-wear-resistance iron aluminate cementing material and a preparation method thereof. The cementing material clinker comprises the following mineral phases in percentage by mass: 30-50% of calcium ferrous sulfide aluminate (C4A3-xFx, x is greater than or equal to 0.3 and less than or equal to 0.7), 25-43% of calcium ferrous aluminate (C6AF2), 20-25% of dicalcium silicate (C2S) and the balance of inevitable impurities, and Na, P, B and Sm elements are in solid solution in the calcium ferrous sulfide aluminate mineral phases, the calcium ferrous aluminate mineral phases and the dicalcium silicate mineral phases. The ferrous aluminate cementing material clinker disclosed by the invention not only can avoid the problem that the strength of a ferrous aluminate cementing material is reduced, but also can improve the stability of a C2S mineral phase and improve the early mechanical strength of the cementing material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of cementitious material clinker preparation, and in particular to an early-strength, high-strength and high-wear-resistant ferroaluminate cementitious material and a preparation method thereof. Background Art

[0002] Compared with sulphoaluminate cementitious materials, more Fe2O3 is introduced into the clinker of ferroaluminate cementitious materials during calcination. Fe2O3 can be dissolved in calcium sulphoaluminate and calcium aluminoferrite minerals. The above minerals can be hydrated to form iron glue, iron-containing calcium sulfonate and hydrated calcium aluminoferrite. These hydration products have better wear resistance and chloride ion solidification ability. However, the raw material used to produce ferroaluminate cementitious materials has a high content of Fe2O3, which leads to an increase in the amount of Fe2O3 dissolved in the mineral phases of calcium sulphoaluminate and calcium aluminoferrite in the ferroaluminate cementitious materials, a decrease in the number of oxygen active sites in the minerals, and a decrease in the hydration activity of the minerals. In addition, since the initial hydration products of calcium aluminoferrite are mainly C4(AF)H 13 , in the later stage of hydration, it transforms to C3(AF)H6, resulting in strength shrinkage. This is due to the fact that C4(AF)H 13 It is a metastable hydration product, which gradually transforms into the more stable C3(AF)H6. In addition, due to the high content of Fe2O3 in the ferroaluminate cementitious material, when the ferroaluminate cementitious material is prepared by high-temperature calcination, iron is dissolved into the C2S crystal, which can increase the stability of β-type C2S, making it difficult to transform into α'-type C2S mineral under high temperature conditions. The C2S in the final cement clinker is basically all in the β-crystalline form, and the hydration activity of β-type C2S is lower than that of α'-type C2S, which leads to the slow growth or even shrinkage of the mechanical properties of the cementitious material in the later stage. Summary of the invention

[0003] In view of the above problems, the present invention provides an early-strength, high-strength, and high-wear-resistant aluminoferrite cementitious material and a preparation method thereof, which can not only avoid the problem of strength shrinkage of aluminoferrite cementitious materials, but also improve the stability of the α'-C2S mineral phase and improve the early mechanical strength of the cementitious material. Specifically, the technical solution of the present invention is as follows.

[0004] Firstly, the present invention discloses an early-strength, high-strength and high-wear-resistant ferroaluminate cementitious material, which comprises the following mineral phases, measured by mass percentage: 30-50% of calcium ferroaluminate sulfide, 25-43% of calcium ferroaluminate (C6AF2), 20-25% of dicalcium silicate (C2S), and the remainder comprises inevitable impurities. In addition, Na, P, B and Sm elements are solid-dissolved in the above-mentioned calcium ferroaluminate sulfide, calcium ferroaluminate and α'-dicalcium silicate mineral phases, and the Na and Sm replace part of the Ca element, and the P and B replace part of the Si element.

[0005] Furthermore, the molecular formula of the calcium ferroaluminate is C4A3-x F x $, 0.3 ≤ x ≤0.7.

[0006] Furthermore, the mass percentage of α'-C2S in the dicalcium silicate is 80-95%.

[0007] Furthermore, the calcium aluminoferrite mineral phase has a crystal form of I2bm, and its activity is higher than that of the calcium aluminoferrite mineral of the Pnma crystal form.

[0008] Furthermore, 5-20% of the mass of gypsum is added to the cementitious material clinker. Optionally, the gypsum includes at least one of dihydrate gypsum, desulfurized gypsum, phosphogypsum, fluorinated gypsum, titanium gypsum, and the like.

[0009] Secondly, the present invention discloses a preparation method of the early-strength, high-strength and high-wear-resistant ferroaluminate cementitious material, which comprises the following steps: using a calcium source, red mud, an aluminum source, a sulfur source, hydroxyapatite, boric acid and samarium oxide as raw materials, then mixing the above raw materials evenly and calcining them, and after completion, rapidly cooling the calcined product to obtain the obtained material.

[0010] Furthermore, the proportions of the components in the raw materials are: 80-100 parts by weight of calcium source, 45-55 parts by weight of red mud, 15-30 parts by weight of aluminum source, 5-25 parts by weight of sulfur source, 1-2 parts by weight of hydroxyapatite, 0.5-1.0 parts by weight of boron source, and 0.05-0.1 parts by weight of samarium source.

[0011] Furthermore, the fineness of the raw materials is 100-200 meshes so that each component can be fully mixed evenly.

[0012] Furthermore, the calcium source includes at least one of limestone, calcium oxide, carbide slag, etc.

[0013] Furthermore, the aluminum source includes at least one of bauxite ore, aluminum ash, etc.

[0014] Furthermore, the sulfur source includes at least one of dihydrate gypsum, desulfurized gypsum, phosphogypsum, fluorinated gypsum, titanium gypsum and the like.

[0015] Furthermore, the boron source includes at least one of boric acid, borax and the like.

[0016] Furthermore, the samarium source includes at least one of samarium oxide, samarium hydroxide, samarium carbonate, etc.

[0017] Furthermore, the calcination treatment temperature is 1070-1170° C. and the time is 5-10 min.

[0018] Compared with the prior art, the technical solution of the present invention has at least the following beneficial effects: (1) Calcium ferroaluminate (C4A) in the ferroaluminate cementitious material prepared by the present invention 3-x F x $, 0.3 ≤ x ≤0.7) and calcium aluminoferrite (C6AF2), which increase the oxygen active sites of these two mineral phases, making them more susceptible to water erosion, thereby improving their hydration activity, so that the calcium aluminoferrite can be completely hydrated at a hydration age of three days, and the calcium aluminoferrite can be completely hydrated at a hydration age of seven days, effectively improving the early mechanical strength of the cementitious material. This is because: the valence of the Na and Sm elements are +1 and +3, respectively. After the two elements jointly replace part of the +2-valent Ca element, the crystal valence can be balanced, thereby increasing the number of oxygen active sites in the mineral and improving the mineral activity. The valence of the P and B elements is +5 and +3, respectively. After the two elements jointly replace the +4-valent Si element, the crystal valence can also be balanced, thereby increasing the number of oxygen active sites in the mineral and improving the mineral activity. In addition, the above elements cause calcium aluminoferrite to directly form C3(A,F)H6 during the hydration reaction, without C4(A,F)H 13 , avoiding the late hydration C4(A,F)H 13 The strength reduction phenomenon caused by the transformation to C3(A,F)H6 is because these elements can promote the reaction of calcium ions in the hydration liquid phase to form insoluble Ca3(PO4)2 and slightly soluble Ca3(BO3)2, resulting in a decrease in the calcium ion concentration in the hydration liquid phase, making it easier for the ions in the hydration liquid phase to react to form C3(A,F)H6 with a low calcium content.

[0019] (2) After the Na, P, B and Sm elements are dissolved in the α'-C2S mineral phase in the ferroaluminate cementitious material prepared by the present invention, its stability is significantly enhanced. This is because during the rapid cooling of the clinker, the α'-C2S therein tends to transform into β-C2S, and the above elements hinder the movement of atoms inside the crystal when the clinker is cooled, thereby stabilizing the highly active α'-C2S and preventing the α'-C2S from transforming into other crystal forms, thereby significantly improving the mechanical strength of the cementitious material clinker in the middle and late stages.

[0020] (3) The alumina-ferrocement material prepared by the present invention has no efflorescence phenomenon, which is because there are a large amount of AFt and AFm in the hydration product of the cementitious material of the present invention, which have a good solidification effect on alkali, thereby inhibiting efflorescence. In addition, since the Fe2O3 content in the cementitious material of the present invention is relatively high, its hydration to form ferric glue, iron-containing calcium aluminate and hydrated calcium alumina-ferrocement can significantly improve the wear resistance. The test results show that the wear resistance of the cementitious material of the present invention is 120-200% higher than that of ordinary silicate cement cementitious material. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.

[0022] Figure 1 The XRD spectrum of the ferroaluminate cementitious material clinker prepared in Example 1 is as follows.

[0023] Figure 2 The XRD pattern of the ferroaluminate cementitious material clinker prepared in Example 2 below. DETAILED DESCRIPTION

[0024] The present invention will be further described below in conjunction with specific examples. It should be understood that these examples are only used to illustrate the present invention and are not intended to limit the scope of the present invention. The experimental methods in the following examples without specifying specific conditions are usually carried out under conventional conditions or under conditions recommended by the manufacturer.

[0025] Unless otherwise defined, all professional and scientific terms used in the present invention have the same meanings as those familiar to those skilled in the art. The reagents or raw materials used in the present invention can be purchased through conventional channels. Unless otherwise specified, the reagents or raw materials used in the present invention are used in a conventional manner in the art or in accordance with the product instructions.

[0026] In addition, any method and material similar or equivalent to the described content can be applied to the method of the present invention. The technical solution of the present invention is further described in conjunction with the accompanying drawings and specific embodiments.

[0027] Example 1 A method for preparing an early-strength, high-strength and high-wear-resistant ferroaluminate cementitious material comprises the following steps: (1) Weigh the raw materials according to the following proportions: 90 parts by weight of limestone, 50 parts by weight of Bayer red mud, 25 parts by weight of bauxite, 12 parts by weight of desulfurized gypsum, 1.2 parts by weight of hydroxyapatite, 0.75 parts by weight of boric acid, and 0.06 parts by weight of samarium oxide. The limestone, Bayer red mud, bauxite, and desulfurized gypsum are all from Shandong Aluminum Environmental New Materials Co., Ltd., the same below.

[0028] (2) Grind the above raw materials and pass them through a 100-mesh sieve. Add water to the obtained mixture and press it into a raw cake. Then heat the raw cake to 1120°C at a heating rate of 10°C / min and calcine for 7 min. Then, air-cool the calcined product to room temperature. After completion, grind the cooled product and pass it through a 200-mesh sieve to obtain aluminoferroic cementitious material clinker.

[0029] The alumina-ferrocement material clinker prepared in this embodiment was subjected to XRD test (eg Figure 1The results show that the mineral phase composition of the ferroaluminate cementitious material clinker in this embodiment includes: calcium ferroaluminate (C4A 2.5 F 0.5 The invention relates to a calcium silicate having a mass percentage of 42.16 wt.% and 23.54 wt.% of calcium aluminoferrite (C6AF2), and a calcium silicate having a mass percentage of 93.08 wt.% and the remainder including inevitable impurities. The crystal form of the calcium aluminoferrite mineral phase is I2bm.

[0030] Performance test: (1) According to GB / T17671-2021 "Test method for strength of cementitious materials (ISO method)", the 3d, 7d and 28d compressive strength of the ferroaluminate cementitious material prepared in this embodiment was tested. (2) According to T0567-2005 "Test method for wear resistance of cementitious materials concrete", the wear resistance of the ferroaluminate cementitious material prepared in this embodiment was tested. (3) The surface of the clean slurry test block prepared from the clinker of the ferroaluminate cementitious material in this embodiment was observed to evaluate its efflorescence. The test results are shown in Table 1 below: Table 1 Performance test results of this embodiment .

[0031] Example 2 A method for preparing an early-strength, high-strength and high-wear-resistant ferroaluminate cementitious material comprises the following steps: (1) Weigh the following raw materials in the following proportions: 87 parts by weight of limestone, 56 parts by weight of Bayer red mud, 32 parts by weight of bauxite, 15 parts by weight of desulfurized gypsum, 1.0 parts by weight of hydroxyapatite, 0.90 parts by weight of boric acid, and 0.07 parts by weight of samarium oxide.

[0032] (2) Grind the above raw materials and pass them through a 100-mesh sieve. Add water to the obtained mixture and press it into a raw cake. Then heat the raw cake to 1070°C at a heating rate of 10°C / min and calcine for 10 min. Then, cool the calcined product to room temperature by air cooling. After completion, grind the cooled product and pass it through a 200-mesh sieve to obtain aluminoferroic cementitious material clinker.

[0033] The alumina-ferrocement material clinker prepared in this embodiment was subjected to XRD test (eg Figure 2 The results show that the mineral phase composition of the ferroaluminate cementitious material clinker in this embodiment includes: calcium ferroaluminate (C4A 2.3 F 0.7The mineral phase comprises 49.98wt.% of calcium aluminoferrite (C6AF2) 28.41wt.% of calcium silicate and 20.03wt.% of dicalcium silicate (of which α'-C2S accounts for 95.02wt.%), and the remainder includes inevitable impurities, and the crystal form of the calcium aluminoferrite mineral phase is I2bm.

[0034] Performance test: (1) According to GB / T17671-2021 "Test method for strength of cementitious materials (ISO method)", the 3d, 7d and 28d compressive strength of the ferroaluminate cementitious material prepared in this embodiment was tested. (2) According to T0567-2005 "Test method for wear resistance of cementitious materials concrete", the wear resistance of the ferroaluminate cementitious material prepared in this embodiment was tested. (3) The surface of the clean slurry test block prepared from the clinker of the ferroaluminate cementitious material in this embodiment was observed to evaluate its efflorescence. The test results are shown in Table 2 below: Table 2 Performance test results of this embodiment .

[0035] Example 3 A method for preparing an early-strength, high-strength and high-wear-resistant ferroaluminate cementitious material comprises the following steps: (1) Weigh the following raw materials in the following proportions: 85 parts by weight of calcium oxide, 48 parts by weight of Bayer red mud, 28 parts by weight of bauxite, 14 parts by weight of dihydrate gypsum, 0.90 parts by weight of hydroxyapatite, 0.45 parts by weight of boric acid, and 0.04 parts by weight of samarium oxide.

[0036] (2) Grind the above raw materials and pass them through a 200-mesh sieve. Add water to the obtained mixture and press it into a raw cake. Then heat the raw cake to 1170°C at a heating rate of 10°C / min and calcine for 5 min. Then, air-cool the calcined product to room temperature. After completion, grind the cooled product and pass it through a 200-mesh sieve to obtain aluminoferroic cementitious material clinker.

[0037] The alumina-ferrocement material clinker prepared in this embodiment was subjected to XRD test and Rietveld quantitative analysis. The results showed that the mineral phase composition of the alumina-ferrocement material clinker in this embodiment included: calcium ferroaluminate sulfide (C4A 2.7 F 0.3 The mineral phase comprises 46.21wt.% of calcium aluminoferrite (C6AF2) and 25.01wt.% of calcium silicate (of which α'-C2S accounts for 80.07wt.%), and the remainder includes inevitable impurities, and the crystal form of the calcium aluminoferrite mineral phase is I2bm.

[0038] Performance test: (1) According to GB / T17671-2021 "Test method for strength of cementitious materials (ISO method)", the 3d, 7d and 28d compressive strength of the ferroaluminate cementitious material prepared in this embodiment was tested. (2) According to T0567-2005 "Test method for wear resistance of cementitious materials concrete", the wear resistance of the ferroaluminate cementitious material prepared in this embodiment was tested. (3) The surface of the clean slurry test block prepared from the clinker of the ferroaluminate cementitious material in this embodiment was observed to evaluate its efflorescence. The test results are shown in Table 3 below: Table 3 Performance test results of this embodiment .

[0039] Example 4 A method for preparing an early-strength, high-strength and high-wear-resistant ferroaluminate cementitious material comprises the following steps: (1) Weigh the following raw materials in the following proportions: 98 parts by weight of limestone, 66 parts by weight of Bayer red mud, 23 parts by weight of bauxite, 9 parts by weight of desulfurized gypsum, 1.0 parts by weight of hydroxyapatite, 0.80 parts by weight of boric acid, and 0.05 parts by weight of samarium oxide.

[0040] (2) Grind the above raw materials and pass them through a 100-mesh sieve. Add water to the obtained mixture and press it into a raw cake. Then heat the raw cake to 1070°C at a heating rate of 10°C / min and calcine for 10 min. Then, cool the calcined product to room temperature by air cooling. After completion, grind the cooled product and pass it through a 200-mesh sieve to obtain aluminoferroic cementitious material clinker.

[0041] The alumina-ferrocement material clinker prepared in this embodiment was subjected to XRD test and Rietveld quantitative analysis. The results showed that the mineral phase composition of the alumina-ferrocement material clinker in this embodiment included: calcium ferroaluminate sulfide (C4A 2.6 F 0.4 The mineral phase comprises 29.95wt.% of calcium aluminoferrite (C6AF2) 43.03wt.% of calcium silicate and 23.58wt.% of dicalcium silicate (of which α'-C2S accounts for 91.83wt.%), and the remainder includes inevitable impurities, and the calcium aluminoferrite mineral phase has a crystal form of I2bm.

[0042] Performance test: (1) According to GB / T17671-2021 "Test method for strength of cementitious materials (ISO method)", the 3d, 7d and 28d compressive strength of the ferroaluminate cementitious material prepared in this embodiment was tested. (2) According to T0567-2005 "Test method for wear resistance of cementitious materials concrete", the wear resistance of the ferroaluminate cementitious material prepared in this embodiment was tested. (3) The surface of the pure slurry test block prepared from the clinker of the ferroaluminate cementitious material in this embodiment was observed to evaluate its efflorescence. The test results are shown in Table 4 below: Table 4 Performance test results of this embodiment .

[0043] Example 5 A method for preparing an early-strength, high-strength and high-wear-resistant ferroaluminate cementitious material comprises the following steps: (1) Weigh the raw materials according to the following proportions: 89 parts by weight of limestone, 485 parts by weight of Bayer red mud, 31 parts by weight of bauxite, 16 parts by weight of desulfurized gypsum, 1.3 parts by weight of hydroxyapatite, 0.65 parts by weight of borax, and 0.05 parts by weight of samarium hydroxide.

[0044] (2) Grind the above raw materials and pass them through a 150-mesh sieve. Add water to the obtained mixture and press it into a raw cake. Then heat the raw cake to 1100°C at a heating rate of 10°C / min and calcine for 8 min. Then, cool the calcined product to room temperature by air cooling. After completion, grind the cooled product and pass it through a 300-mesh sieve to obtain the ferroaluminate cementitious material clinker.

[0045] The alumina-ferrocement material clinker prepared in this embodiment was subjected to XRD test and Rietveld quantitative analysis. The results showed that the mineral phase composition of the alumina-ferrocement material clinker in this embodiment included: calcium ferroaluminate sulfide (C4A 2.5 F 0.5 $) 40.18wt.%, calcium aluminoferrite (C6AF2) 36.22wt.%, dicalcium silicate 21.64wt.% (of which α'-C2S accounts for 87.79wt.%), and the remainder including unavoidable impurities is equal.

[0046] Performance test: (1) According to GB / T17671-2021 "Test method for strength of cementitious materials (ISO method)", the 3d, 7d, and 28d compressive strength of the ferroaluminate cementitious material prepared in this embodiment was tested. (2) According to T0567-2005 "Test method for wear resistance of cementitious materials concrete", the wear resistance of the ferroaluminate cementitious material prepared in this embodiment was tested. (3) The surface of the pure slurry test block prepared from the clinker of the ferroaluminate cementitious material in this embodiment was observed to evaluate its efflorescence. The test results are shown in Table 5 below: Table 5 Performance test results of this embodiment .

[0047] Example 6 A method for preparing an early-strength, high-strength and high-wear-resistant ferroaluminate cementitious material comprises the following steps: (1) Weigh the following raw materials in the following proportions: 95 parts by weight of limestone, 61 parts by weight of Bayer red mud, 22 parts by weight of bauxite, 11 parts by weight of desulfurized gypsum, 1 part by weight of hydroxyapatite, 0.80 parts by weight of boric acid, and 0.07 parts by weight of samarium carbonate.

[0048] (2) Grind the above raw materials and pass them through a 200-mesh sieve. Add water to the obtained mixture and press it into a raw cake. Then heat the raw cake to 1150°C at a heating rate of 10°C / min and calcine for 10 min. Then, air-cool the calcined product to room temperature. After completion, grind the cooled product and pass it through a 300-mesh sieve to obtain aluminoferroic cementitious material clinker.

[0049] The alumina-ferrocement material clinker prepared in this embodiment was subjected to XRD test and Rietveld quantitative analysis. The results showed that the mineral phase composition of the alumina-ferrocement material clinker in this embodiment included: calcium ferroaluminate sulfide (C4A 2.3 F 0.7 $) 35.41wt.%, calcium aluminoferrite (C6AF2) 42.07wt.%, dicalcium silicate 20.72wt.% (of which α'-C2S accounts for 94.33wt.%), and the remainder including unavoidable impurities is equal.

[0050] Performance test: (1) According to GB / T17671-2021 "Test method for strength of cementitious materials (ISO method)", the 3d, 7d, and 28d compressive strength of the ferroaluminate cementitious material prepared in this embodiment was tested. (2) According to T0567-2005 "Test method for wear resistance of cementitious materials concrete", the wear resistance of the ferroaluminate cementitious material prepared in this embodiment was tested. (3) The surface of the pure slurry test block prepared from the clinker of the ferroaluminate cementitious material in this embodiment was observed to evaluate its efflorescence. The test results are shown in Table 5 below: Table 6 Performance test results of this embodiment .

[0051] Example 7 A method for preparing an early-strength, high-strength, and high-wear-resistant ferroaluminate cementitious material is the same as the above-mentioned embodiment 1, except that samarium oxide is not added to the preparation raw materials of this embodiment.

[0052] Performance test: (1) According to GB / T17671-2021 "Test method for strength of cementitious materials (ISO method)", the 3d, 7d and 28d compressive strength of the ferroaluminate cementitious material prepared in this embodiment was tested. (2) According to T0567-2005 "Test method for wear resistance of cementitious materials concrete", the wear resistance of the ferroaluminate cementitious material prepared in this embodiment was tested. (3) The surface of the clean slurry test block prepared from the clinker of the ferroaluminate cementitious material in this embodiment was observed to evaluate its efflorescence. The test results are shown in Table 7 below: Table 7 Performance test results of this embodiment .

[0053] Example 8 A method for preparing an early-strength, high-strength and high-wear-resistant ferroaluminate cementitious material is the same as the above-mentioned embodiment 1, except that hydroxyapatite is not added to the preparation raw materials of this embodiment.

[0054] Performance test: (1) According to GB / T17671-2021 "Test method for strength of cementitious materials (ISO method)", the 3d, 7d and 28d compressive strength of the ferroaluminate cementitious material prepared in this embodiment was tested. (2) According to T0567-2005 "Test method for wear resistance of cementitious materials concrete", the wear resistance of the ferroaluminate cementitious material prepared in this embodiment was tested. (3) The surface of the pure slurry test block prepared from the clinker of the ferroaluminate cementitious material in this embodiment was observed to evaluate its efflorescence. The test results are shown in Table 8 below: Table 8 Performance test results of this embodiment .

[0055] Example 9 A method for preparing an early-strength, high-strength and high-wear-resistant ferroaluminate cementitious material is the same as the above-mentioned embodiment 2, except that boric acid is not added to the preparation raw materials of this embodiment.

[0056] Performance test: (1) According to GB / T17671-2021 "Test method for strength of cementitious materials (ISO method)", the 3d, 7d and 28d compressive strength of the ferroaluminate cementitious material prepared in this embodiment was tested. (2) According to T0567-2005 "Test method for wear resistance of cementitious materials concrete", the wear resistance of the ferroaluminate cementitious material prepared in this embodiment was tested. (3) The surface of the pure slurry test block prepared from the clinker of the ferroaluminate cementitious material in this embodiment was observed to evaluate its efflorescence. The test results are shown in Table 9 below: Table 9 Performance test results of this embodiment .

[0057] Example 10 A method for preparing an early-strength, high-strength, and high-wear-resistant ferroaluminate cementitious material is the same as the above-mentioned Example 3, except that hydroxyapatite, boric acid, and samarium oxide are not added to the preparation raw materials of this embodiment, and red mud is replaced by iron tailings.

[0058] Performance test: (1) According to GB / T17671-2021 "Test method for strength of cementitious materials (ISO method)", the 3d, 7d and 28d compressive strength of the ferroaluminate cementitious material prepared in this embodiment was tested. (2) According to T0567-2005 "Test method for wear resistance of cementitious materials concrete", the wear resistance of the ferroaluminate cementitious material prepared in this embodiment was tested. (3) The surface of the clean slurry test block prepared from the clinker of the ferroaluminate cementitious material in this embodiment was observed to evaluate its efflorescence. The test results are shown in Table 10 below: Table 10 Performance test results of this embodiment .

[0059] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention is described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. An early-strength, high-strength, high-wear-resistant ferroaluminate cementitious material, characterized in that: Measured in percentage by mass, the cementitious material clinker comprises the following mineral phases: 30-50% of calcium ferroaluminate, 25-43% of calcium ferroaluminate, 20-25% of dicalcium silicate, and the remainder comprises inevitable impurity phases, and the above-mentioned calcium ferroaluminate, calcium ferroaluminate and dicalcium silicate mineral phases all contain Na, P, B and Sm elements in solid solution, and the Na and Sm replace part of the Ca element, and P and B replace part of the Si element.

2. The early-strength, high-strength, high-wear-resistant ferroaluminate cementitious material according to claim 1, characterized in that: The molecular formula of the calcium ferroaluminate is C4A 3-x F x $, 0.3 ≤ x ≤0.

7.

3. The early-strength, high-strength, high-wear-resistant ferroaluminate cementitious material according to claim 1, characterized in that: The mass percentage of α'-C2S in the dicalcium silicate is 80-95%.

4. The early-strength, high-strength, high-wear-resistant ferroaluminate cementitious material according to claim 1, characterized in that: As described above, its activity is higher than that of Pnma crystal type calcium aluminoferrite mineral.

5. The early-strength, high-strength, high-wear-resistant ferroaluminate cementitious material according to any one of claims 1 to 4, characterized in that: The cementitious material clinker is also mixed with gypsum in an amount of 5 to 20% of its mass; Optionally, the gypsum includes at least one of dihydrate gypsum, desulfurized gypsum, phosphogypsum, fluorinated gypsum and titanium gypsum.

6. The method for preparing the early-strength, high-strength and high-wear-resistant ferroaluminate cementitious material according to any one of claims 1 to 5, characterized in that: The method comprises the following steps: taking calcium source, red mud, aluminum source, sulfur source, hydroxyapatite, boric acid and samarium oxide as raw materials, then uniformly mixing the raw materials and calcining them, and after completion, rapidly cooling the calcined product to obtain the obtained product.

7. The method for preparing the early-strength, high-strength and high-wear-resistant ferroaluminate cementitious material according to claim 6, characterized in that: The proportions of the components in the raw materials are: 80-100 parts by weight of calcium source, 45-55 parts by weight of red mud, 15-30 parts by weight of aluminum source, 5-25 parts by weight of sulfur source, 1-2 parts by weight of hydroxyapatite, 0.5-1.0 parts by weight of boron source, and 0.05-0.1 parts by weight of samarium source; optionally, the fineness of the raw materials is 100-200 mesh.

8. The method for preparing the early-strength, high-strength and high-wear-resistant ferroaluminate cementitious material according to claim 6, characterized in that: The calcium source includes at least one of limestone, calcium oxide, and carbide slag; optionally, the aluminum source includes at least one of bauxite and aluminum ash.

9. The method for preparing the early-strength, high-strength and high-wear-resistant ferroaluminate cementitious material according to claim 6, characterized in that: The sulfur source includes at least one of dihydrate gypsum, desulfurized gypsum, phosphogypsum, fluorinated gypsum and titanium gypsum.

10. The method for preparing the early-strength, high-strength and high-wear-resistant ferroaluminate cementitious material according to any one of claims 6 to 9, characterized in that: The samarium source includes at least one of samarium oxide, samarium hydroxide and samarium carbonate; Optionally, the boron source includes at least one of boric acid and borax; Optionally, the calcination treatment is performed at a temperature of 1070-1170° C. and for a time of 5-10 min.